Implementasi Akad Pembiayaan Syariah pada GALA (Gadai Tradisional) - Ikhsan Fajri; Muksal (Cyber Media Indonesia, 2021)
Islamic financial institutions instruments are required to synergize and provide new patterns and ideas in reconstructing previous ideas with the current context so that Islamic financial instruments can be applied by the current generation. This study uses qualitative research methods. The purpose of this study is to identify the implementation of the sharia funding agreement on gala. The research approach used in this study is a phenomenological approach. The type of data used is primary data. Data collection techniques use interviews and observation. The practice of traditional gala found in the lives of southwest Acehnese people was built from generation to generation from the 16th century to the present, approaching the pattern of contract existing in the Islamic economic system where one of them is a mudharabah contract. This contract is expected to be an alternative solution for islamic financial institutions in the future for productive financing which is based on the business practices of the Southwest Aceh community that are local wisdom.